Fat Embolism Syndrome Mimicking a COVID-19 Infection - Alexandru Leonard Alexa; Adela Hilda Onutu (Case Reports in Critical Care)
Fat embolism syndrome (FES) is a multiple organ disorder that can appear after pelvic and long bone fractures. The most common clinical finding is hypoxia, accompanied by diffuse petechiae, alveolar infiltrates, altered mental status, fever, polypnea, and tachycardia. We present a mild FES case on a 32-year-old man with no medical history admitted for an orthopedic procedure, following both tibia and fibulae fractures. Thirty hours postoperatively, he developed respiratory failure with altered mental status and needed admission in the intensive care unit. The chest radiography and later chest tomography raised the suspicion of a COVID-19 disease, even if our first suspicion was FES. After being carefully investigated in a dedicated COVID-19 ward and three negative RT-PCR SARS-CoV-2 tests, he returned to continue supportive treatment in the orthopedic intensive care ward. His evolution was favorable with discharge at ten days, without sequelae. In the context of the SARS CoV-2 pandemic, differential diagnosis has become an increasingly challenging process. Added to the variety of preexisting respiratory diseases and disorders, the COVID-19 infection, with its symptomatology so similar to multiple other pulmonary diseases, must not cloud our clinical judgement.